A case control study to compare the effect of dynamisation of tibia nail in union of tibia shaft fracture versus non-dynamisation - Gunay, Siddharth; Avhad, Tanmay A.; Tungenwar, Shubham; Jethlia, Sanket (International Journal of Research in Orthopaedics, 2024)
Background: Tibial shaft fractures are commonly treated with intramedullary nails (IMN), with union rates of 90-100%, but complications such as delayed union occur in up to 40%. The rise of technology and urbanization has led to an increase in road traffic injuries and deaths. The treatment of distal tibia fractures has undergone various modifications over the years, with emphasis on preserving local biology and soft tissue handling. Methods: A retrospective case-control study involving 132 patients with closed or open grade 1 tibia shaft fractures was conducted from September 2021 to May 2022. Patients received tibia IMN with either dynamic locking (group A) or static (group B). Patients were evaluated for fracture healing and clinical condition, with variables including presence or absence of union and time to union. Follow-up clinical evaluations were conducted monthly for six months. Results: The association between union of bones seen at 1.5 and 3 months between group A and group B was extremely statistically significant (p<0.0001). Conclusions: Intramedullary nailing with dynamic nailing assemblies is safe and effective for closed or type I open tibial fractures with limited comminution. This approach may reduce complications and re-operations and allow for early weight-bearing. Proper management of tibial fractures requires an interprofessional team.